Chironomid sentinel cards: an easy-to-apply method for assessing predation rates freshwater (agro)ecosystems - Pérez-Méndez, Néstor; Echeverría-Progulakis, Sebastián; Llevat, Raül; Alcaraz, Carles; Martínez-Eixarch, Maite; Catala-Forner, Mar (Frontiers in Ecology and Evolution, 2024)
Global change is eroding freshwater biodiversity at higher rates than in any other ecosystem, potentially entailing a parallel degradation of ecosystem functions such as the predation function. However, the relationships between biodiversity and predation effectiveness remain poorly explored in freshwater ecosystems, largely due to the unavailability of easy-to-apply methods that allow to characterize the predation function under real-field conditions. Here we proposed the chironomid sentinel cards as a fast, reliable, and standardized method to estimate predation rates in aquatic ecosystems. Briefly, by easily gluing a set of commercially available chironomid larvae to a plastic card and offering them to aquatic predators during a timelapse we can quantify removal rates, and hence the predation function. As an indicator of the usefulness of the method, we additionally assessed whether the use of chironomid sentinel cards allows to link the estimated predation rates to three descriptors of predator assemblages: i) taxa richness, ii) Hill evenness, and iii) abundance of aquatic predators. To do that, we combined a thorough sampling of aquatic macroinvertebrate predators with a large deployment of chironomid sentinel cards across 12 flooded rice fields during three different stages of the rice phenological cycle. Our results show that the three biodiversity indexes were positively related to the predation rate estimates, highlighting the sensibility of the method to changes in predator assemblages. We therefore conclude that the methodology is suitable to assess potential biodiversity-predation links under field aquatic conditions. We advocate to use the chironomid sentinel cards as an easy-to-apply, fast, and standardized method that allows comparisons of predation effectiveness across different shallow freshwater ecosystems.